Hepatoprotective and antioxidant activities of dry standardized extract of Apeiba tibourbou Aubl, in mice - Melo, Dorcas F. A.; Melo, Davi S.; Parente, Leila M. L.; Silva, Marina A. C.; Cunha, Luiz C.; Conceição, Edemilsom C.; Júnior, Ruy S. L. (Brazilian Journal of Veterinary Pathology, 2017)
Due to its chemical composition and use in folk medicine, the dry standardized extract of Apeiba tibourbou Aubl. (Tiliaceae) leaves (DSEAT) was tested to assess its hepatoprotective activity against carbon tetrachloride (CCl4)-induced hepatotoxicity in mice. The animals were treated with DSEAT previously for 7 days, at doses of 25, 50, 100, 200, and 400 mg/kg and 18 mg/kg of rosmarinic acid; the liver damage was induced by administering CCl4 intraperitoneally (i.p.) at days 3 and 7, and 1 h before treating with DSEAT. The hepatoprotective activity was assessed using various biochemical assays such as alanine transaminase (ALT), aspartate transaminase (AST), alkaline phosphatase (ALP), gamma-glutamyltransferase (GGT), malondialdehyde (MDA) and histopatological studies. DSEAT doses of 400, 200, and 100 mg/kg were not capable of protecting the liver against CCl4. However, the dose of 50 mg/kg reduced AST by 31.50% the dose of 25 mg/kg reduced GGT by 57.18% compared to the CCl4 (p < 0.05). In the liver, DSEAT dose of 50 mg/kg and rosmarinic acid reduced MDA by 27.45% and 63.61%, respectively, whereas in plasma, MDA was reduced in all the groups treated with DSEAT and rosmarinic acid. In conclusion, DSEAT exhibits hepatoprotective effect only at low doses and antioxidant activity in vivo after peroral administration. The experimental protocol was approved by the Animal Research Ethics Committee of UFG (CEUA, no. 177/2011).